Progress on Gut Health Maintenance and Antibiotic Alternatives in Broiler Chicken Production - Zhu, Qidong; Sun, Peng; Zhang, Bingkun; Kong, LingLian; Xiao, Chuanpi; Song, Zhigang (Frontiers in Nutrition, 2021)
The perturbation of gut health is a common yet unresolved problem in broiler chicken production. Antibiotics used as growth promoters have remarkably improved the broiler production industry with high feed conversion efficiency and reduced intestinal problems. However, misuse of antibiotics has also led to the increase in the development of antibiotic resistance and antibiotic residues in the meat. Many countries have enacted laws prohibiting the use of antibiotics in livestock production because of increasing concerns by consumers and the public. Consequently, one of the most significant discussions in the poultry industry currently is antibiotic-free livestock production. However, the biggest challenge in animal husbandry globally is complete removal of antibiotics. The necessity to venture into antibiotic-free production has led researchers to look for alternatives to antibiotics in broiler chicken production. Many strategies can be used to replace the use of antibiotics in broiler farming. In recent years, many studies have been conducted to identify functional feed additives with similar beneficial effects as antibiotic growth promoters. Attention has been focused on prebiotics, probiotics, organic acids, emulsifiers, enzymes, essential oils, tributyrin, and medium-chain fatty acids. In this review, we focus on recent discoveries on gut health maintenance through use of these functional feed additives as alternatives to antibiotics in the past 10 years to provide novel insights into the design of antibiotic-free feeds.